EFFECT OF INTERNSHIPS ON PRE-SERVICE TEACHERS’ CONCEPTIONS OF PLANNING İN PHYSICAL EDUCATION - Viciana, Jesus; Mayorga-Vega, Daniel (European Scientific Journal, ESJ, 2013)
The pre-service teacher (PT) training is a fundamental stage where the essential competencies of teaching are developed. The aim of this study was to find the effect of an internship on the PT’s conception of the planning of Physical Education (PE). 149 PTs from the University of Granada participated (22.3 aged). A quasi-experimental design pre-post was used. An ad hoc questionnaire previously validated and a semi-structured interview after the process were both employed to measure the PT’s conceptions. Results showed that before the internship, planning was the most important phase for the PT. After the internship, intervention significantly increased with regard to the pretest and became higher than planning. A significant increase of doubts about planning design and interactive decision-making inside the PE classes were also detected. The internship makes the teacher aware of the problems in coordinating theory and practice, thus causing important changes related to teaching PE.